Patch-burn grazing increases habitat heterogeneity and biodiversity of small mammals in managed rangelands - Ricketts, Andrew M.; Sandercock, Brett K. (My University, 2017)
Habitat heterogeneity is a key driver of biodiversity in many ecosystems. Wildlife inhabiting the native prairies of North America evolved in a heterogeneous mosaic of habitat conditions created by fire and grazing by native ungulates. Current rangeland management practices in the tallgrass prairie ecosystem evenly distribute fire and grazing across management units and promote homogeneous habitat conditions. Patch-burn grazing is a rangeland management strategy that seeks to restore heterogeneity to rangelands via fire-grazing interactions. Our 3.5-year study tested the effects of patch-burn grazing on habitat heterogeneity and small mammal community dynamics in the Flint Hills ecoregion of eastern Kansas. To study the ecological effects of patch-burn grazing, we sampled habitat conditions and the small mammal community. We assessed habitat conditions once each growing season in a negative control that was annually burned and grazed, a positive control that was burned every four years and ungrazed, and within each of three units of a patch-burn grazing experiment (PBG) managed with rotational fire. Habitat conditions were significantly different among treatments, and a principal components analysis showed that the patch-burn grazing treatment had higher canopy cover of forbs and habitat heterogeneity than our two control units. To sample the small mammal community, we conducted monthly live trapping of small mammals on two randomly located trap grids in each of our two controls and three units of our PBG treatment. Small mammal diversity was significantly higher in the patch-burn grazing treatment and in the positive control, vs. the negative control. Moreover, a canonical correspondence analysis showed that a fire-grazing interaction was the major driver structuring small mammal communities. Patch-burn grazing is an effective strategy for restoring heterogeneity to vegetative structure and composition, and can increase biodiversity of small mammals in managed rangelands in the tallgrass prairie ecosystem. © 2016 Ricketts and Sandercock.
Citation: Ricketts, A. M., & Sandercock, B. K. (2016). Patch-burn grazing increases habitat heterogeneity and biodiversity of small mammals in managed rangelands. Ecosphere, 7(8). doi:10.1002/ecs2.1431
Keywords: Fire; Heterogeneity; Pyric Herbivory; Rangeland Management; Rodent; Tallgrass Prairie